FORMULATION, OPTIMIZATION AND CHARACTERIZATION OF ZIPRASIDONE NANOCRYSTALS PREPARED BY MEDIA MILLING TECHNIQUE - Gauniya, Anju; Mazumder, Rupa; Pathak, Kamla (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: Today, nanotechnology has a variety of application areas. Pharmacy is one of the most important application fields of nanotechnology. Preparation of nano-particular drug-delivery system, such as nano-crystals improve the solubility and bio-availability of poorly water soluble drugs. Methods: Ziprasidone (ZIP) is a low water soluble drug (Bio-pharmaceutical classification system) and is used as a lipid regulating agent. In this study, a rapid and simple media milling method was used for the preparation of ziprasidone (ZIP) Nanocrystals. The use of sonication after media milling process reduced the milling time significantly. Different concentrations of stabilizers (Kollidone and Tween 80) were tested in the preparation of ZIP nanocrystals. The finest ZIP nanocrystals were obtained by 4 g ZIP, 4 g kollidone and 4 g Tween 80. Results: The size and zeta potential of the finest ZIP nanocrystals were 238.2±2.5 nm and-19.6±0.1 mv, respectively. The morphology of dried ZIP nanocrystals was observed using scanning electron microscopy. Differential scanning calorimetry of ZIP and ZIP nanocrystals confirmed that there was no interaction between ZIP and stabilizers. Compared with ZIP, the solubility of ZIP nanocrystals increased significantly. Conclusion: Media milling technology was successfully used for the formulation of poor water soluble drugs. Nano-sized drug particles prepared by media milling technique could improve the solubility and bio-availability of those drugs.